The Current Situation of Digital Transformation's Impact on Workers' Employment Issues - Thanh Truong, Dao; Tien Anh, Tran; Thanh Tuan, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 38 No 3, 2022)
In all aspects of social life, digital transformation brings both challenges and opportunities. The authors make some comments on the digital transformation process in Vietnam and propose some solutions to develop human resources for the digital transformation in Vietnam based on their assessment of the digital transformation processes of some countries around the world. Keywords: Digital transformation, human resources, employees.